PHYSICAL AND MICROBIOLOGICAL PERFOMANCES OF ACIDIFIED FISH MEAL MADE BY DIPPING INTO EXTRACT SOLUTION OF SAUERKRAUT - Sulistiyanto, B.; Nugroho, K. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
An experiment was conducted to examine the influence of soaking time into extract solution ofSauerkraut on physic and microbial performances of acidified fish meal. Sauerkraut extract (LPS'ssollution) was made by fermentation of wastes vegetable market for 6 days. The LPS-extract was used toacidify " ikan rucah" by the method of dipping for 0, 4 and 8 hours. Changes in pH, the total number ofbacteria, fungi and proteolytic bacteria, moisture content, odor, colour and texture were parametersobserved. Results of experiment showed that total bacteria, fungi and proteolytic bacteria of acidifiedfish meal significantly influenced by soaking time (p <0.05). No significantly effect was shown to thephysically performance. LPS-extract in the soaking effectively reduced content of total bacteria, fungiand proteolytic's bacteria in fish meal.